Assessing local and transboundary fine particulate matter pollution and sectoral contributions in Southeast Asia during haze months of 2015–2019 - Fang, Tingting (2024)
While previous studies have investigated haze events over Southeast Asia (SEA), local and transboundary contributions of various emission sources to haze months over the entire SEA have yet to be assessed comprehensively and systematically. We utilized the Particle Source Apportionment Technique (PSAT) to quantify the spatial local, transboundary, and sectoral contributions to PM2.5 over SEA during the haze months of 2015–2019. Results show that local emission contributions accounted for 56.1 % ~ 94.2 % of PM2.5 in Indonesia, Philippines, Vietnam, and Thailand. Transboundary contributions (23.1 % ~ 57.6 %) from Indonesia notably influenced maritime SEA. Vietnam (15.6 % ~ 39.1 %) and super-regional (17.0 % ~ 34.3 %) contributions outside the SEA exerted remarkable impacts on mainland SEA. Among different sectors, fire emissions contributed the most to PM2.5 over maritime SEA (23.0 % ~ 68.6 %) during the studied haze months, whereas residential and other emissions were the main contributors to mainland SEA (27.2 % ~ 36.7 %). Regarding the source species, primary PM2.5 accounted for the majority of PM2.5. VOC and SO2 composed most of the secondary PM2.5 due to massive VOC emissions in the region and the priority reaction of NH3 with sulfuric acid (H2SO4) to form ammonium sulfate. Besides, the intensified haze months in Oct 2015 and Sep 2019 were characterized by more intensive fire emissions in the region and the climatic variability-induced meteorological effects that provided favorable condition for transboundary air pollution (56.9 % and 44.9 %, respectively, for maritime SEA, as well as 46.0 % and 37.7 %, respectively, for mainland SEA in the two studied haze months). The haze months can be attributed to the notable drought conditions amidst global climatic phenomena such as El Niño and positive Indian Ocean Dipole (IOD) in Oct 2015 and Sep 2019, respectively.